Co-gasification of coal and biomass (empty fruit bunch, oil Palm frond, and kempas) in an entrained flow gasifier - Wan Muhamad Syafiq, Wan Ismail (2018)
Gasification is getting more attention as a potential source of alternative energy through the production of syngas, mainly consists of carbon monoxide (CO) and hydrogen (H2) which is suitable for industrial application for highly efficient energy production. The utilization of biomass in a gasification process can reduce the environmental pollution such as the greenhouse gas. Furthermore, biomass co-gasification in an entrained flow gasifier is a promising approach due to its advantages which are (i) higher conversion rate, (ii) high quality tar-free syngas, (iii) can be operated at high temperature, (iv) suitable for various feedstock, and (v) shorter residence time compared with that of other types of gasifier. The influences of temperature, equivalence ratio (ER), and biomass ratio on gas composition, higher heating values (HHV), and cold gas efficiency (CGE) were studied using an entrained flow gasifier. The temperature was controlled between 700 and 900 °C and the ER values were tested in the range of 0.2 to 0.4 for biomass feedstock such as empty fruit bunch (EFB), oil palm frond (OPF) and forest residue Koompassia malaccensis (Kempas). Moreover, the co-gasification of coal and biomass was also studied for the effect of biomass ratio and temperature varied from B0 (100% coal) to B100 (100% biomass) at the temperature of 700 to 900 °C. The co-gasification of various biomass and coal was also studied at the fixed temperature of 900 °C using EFB, OPF, and Kempas in an entrained flow gasifier. The EFB and OPF were collected from Kilang Sawit LCSB Lepar Hilir, Kuantan, and Kempas was collected from Kilang Kayu Gambang, Kuantan. The coal was obtained from TNB Research Bangi. The experiments were performed in a laboratory scale entrained flow gasification system at atmospheric pressure. The samples were put in the reactor on a semi-batch system under the desired airflow rate depending on the ER through manual loading. The air supply to the gasifier was mixed, controlled, and monitored by using two flow meters and two valves. A screw feeder was used to feed the sample and a motor was used to control the speed of the screw feeder. The furnace was cylindrical with an inside diameter of 4.5 cm and a length of 50 cm made by stainless steel which can withstand temperature up to 1100 °C. The gasifier was also equipped with a cyclone where the dirty outlet gas containing ash, char, tar, and dust particles entered the cyclone separator. The cyclone was used to remove ash and chars from the gas and derived them into the primary and secondary ash collectors which were located at the bottom of cyclone. The gas was passed through the cyclone to separate the gas and ash produced from the gasification of biomass. The hot gas was then passed through the condenser to reduce the temperature of gas before the gas was collected in gas sampling bags. Gas chromatography equipped with a thermal conductivity detector (GC–TCD) was used to quantify the gas composition (H2, CO, and CO2) produced from the reaction. The gas compositions may be determined on the basis of the properties given by GC–TCD such as retention time, area, amount/area, and amount. It was found that temperature and ER highly affected the production of syngas using EFB in an entrained flow gasifier. The production of H2 and CO increased while CO2 decreased as the temperature was increased from 700 to 900 °C. Conversely, when the ER was too high, more than 0.3, the production of H2, CO, and CO2 slightly decreased. Furthermore, the HHV and CGE achieved their highest values at 900 °C and ER of 0.3. For the co-gasification of EFB and Adaro coal, when the biomass ratio was increased v between B30 and B50 and the temperature was higher than 850 °C, the production of syngas (H2 and CO) was observed to be at its maximum. However, the CO2 production was seen to be almost unchanged throughout the variation of temperature and biomass ratio. Additionally, the biomass ratio of B30 (30% biomass) was observed to have the maximum HHV and CGE, which implies the presence of the synergistic effects at B30. Furthermore, it was observed that the increase of temperature and biomass ratio influenced the production of syngas from OPF and Kempas. The production of H2 from Kempas was significantly higher compared with that of OPF. Yet, the production of CO and CO2 was nearly the same for both biomasses. At 900 °C, the production of H2 and CO were the highest. Moreover, the HHV and CGE values decreased after reaching the maximum value of ER above 0.3. In addition, it was proven that the biomass ratio highly affected the product syngas from different feedstocks. At B30, it was able to produce the highest amount of syngas, whereas the CO2 production was the highest at B0. Kempas had highest H2 production while EFB had the highest CO production. Similarly, the HHV and CGE values for all sample mixtures were also the highest value at B30, which is another indication of the presence of the synergistic effects at B30.